The influence of light on corrosion of polyaniline coated mild steel - Milica M. Gvozdenović; Branimir Z. Jugović (Zaštita Materijala)
The influence of light of the mild steel corrosion in 3% NaCl solution with polyaniline coating based on the possibilities that polyaniline can generate photoelectrons, even in the laboratory conditions has been investigated.